Analisis Metode Perhitungan Kuantitas Batubara Di Stockpile ROM PT. XYZ - Edwin Harsiga; Siti Hardianti; Ardhi Lufthansyah Hidayat (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2024)
PT XYZ had a method called the on book method to determine the amount of coal tonnage in the ROM stockpile.. This method used the initial stock from the survey calculation resut at the beginning of each month, the incoming coal to the stockpile used truck count method, and the outgoing coal from stockpile used weighbridge calculation. PT XYZ used the survey calculation results at the beginning of the next month rather than on book method result to determine the difference. The Coal tonnages based on survey result data on April 2 was 34.225,454 tons. Whereas, for the on-book calculation, the stock at March 2 was 38.409,083 tons, the coal in 2 March - 2 April was 71.154 tons, and the coal out of 2 March - 2 April was 67.994,52 tons, so the final stock obtained was 41.568,56 tons. The difference from those two methods comparison was 7.343,11 tons. This research discover the factors causing the differences between two methods i.e. incompatible vessel capacity on the truck counts tonnage calculation, disorganized stockpile patterns, declining ROM stockpile base conditions, spilled material, total station tools and weighbridges which had not been calibrated yet.